ANALISIS ISI BUKU MATEMATIKA KURIKULUM 2013 SMP KELAS VIII SEMESTER 1 BERDASARKAN TAKSONOMI TIMSS - Mawarni, Yuyun Evi (Jurnal VARIDIKA, 2019)
The purpose of this research was to determine the composition of the material and practice questions in the mathematics curriculum guide 2013 junior class VIII Semester 1 in terms of content and cognitive domain taxonomy based on TIMSS. This study was a content analysis study (content analysis). The results showed that the analysis of the presentation of the material in terms of the proportion of each content domain, domain algebra occupied the highest proportion with a percentage of 50%, the domain geometry with 33.33% while the percentage of domain data and opportunities with a percentage of 16.67% and there are no material including in the domain of numbers. Judging from the cognitive dimensions, applying knowing domain is (68.42%) and knowing is (21.05%) while the reasoning domain has the 10.53% (the lowest). For analytical presentation of questions in terms of the proportion of each dimension of the content, the material has a percentage of 60.64% algebra, geometry material has persetase 32.13% while the material data and the opportunity have a percentage of 7.23%. From the cognitive dimension to training issues were gained 36 reached the level of cognitive domain knowing 16.98%, 114 reached the level of cognitive domain applying  with 53.77% and 62 about already reached a level of cognitive reasoning domain with  29.25%